The Effects of Vermicompost on Carbon and Nitrogen Availability, C/N ratio and Corn Production Planted in Entisol Coastal Areas - Rezeki, Eksa Tri; Bertham, Yudhy Harini; Hasanudin, Hasanudin; Riwandi; Utami, Kartika (TERRA : Journal of Land Restoration, 2023)
Entisols are soils that are widely used in Indonesia, both for irrigated and rainfed rice fields, for vegetable cultivation, and others. Vermicompost also contains many of the nutrients available to plants and increases soil porosity, soil aeration, and humidity, and controls soil erosion so that it can help in buffering toxins for plants and promoting plant growth. Corn is a cereal crop that is the second most important food crop in Indonesia besides rice. The volume of corn imports is higher than exports, this is due to the high demand for corn but domestic corn production has not been able to fulfill it. The experimental design used was a Randomized Completely Block Design (RCBD), seven levels of vermicompost doses, namely 0; 2.5; 5.0; 7.5; 10; 12.5; and 15 tons ha-1) each repeated 4 times. This study aims to determine the dose of vermicompost fertilizer that can improve the properties of Entisols and yields of maize (Zea mays L.). The application of vermicompost fertilizer with seven dose levels had a significant effect on N nutrient levels in coastal Entisols. Doses of vermicompost were able to increase dry stover weight, cob weight with husk, and cob weight without husk of corn plants.